Effects of superelasticity and plasticity on the spherical indentation response of shape memory alloys : a finite element analysis - Anuja J. (2021)
Instrumented indentation is particularly useful for characterizing the mechanical behavior of shape memory alloys (SMAs), which are often used as 'small volume' elements such as thin films or wires. Deciphering the measured indentation response, which is as such difficult for elastic-plastic materials due to the inhomogeneous state of stress underneath the indenter, becomes more complex for SMAs owing to the simultaneous occurrence of stress induced martensite transformation (SIMT) in conjunction with plastic deformation. In this work, a constitutive model that is able to capture the coupled nature of phase transformation and plastic deformation is employed to study, through finite element analyses, the spherical indentation behavior of SMAs at a temperature above the austenite finish temperature, Af. It is found that the concurrent development of plastic yielding and SIMT leads to slower evolution of martensite volume and a smaller transformed zone size. Also, in the absence of plastic yielding, the proportion of depth recovered by superelasticity is fairly constant. It is also observed, from a systematic comparison with a conventional elastic-plastic material, that the presence of the transformed zone significantly alters the stress distribution beneath the indenter.